2022
DOI: 10.3390/biomedicines10020238
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Human Platelet-Derived Extracellular Vesicles with Secretome Proteins Promotes Regenerative Functions

Abstract: Platelet-rich plasma is a promising regenerative therapeutic with controversial efficacy. We and others have previously demonstrated regenerative functions of human platelet lysate (HPL) as an alternative platelet-derived product. Here we separated extracellular vesicles (EVs) from soluble factors of HPL to understand the mode of action during skin-organoid formation and immune modulation as model systems for tissue regeneration. HPL-EVs were isolated by tangential-flow filtration (TFF) and further purified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
(91 reference statements)
2
22
0
Order By: Relevance
“…As a proof of concept, we visualised the corona formation by super‐resolution microscopy using fluorescent albumin and fluorescent VEGF. During the review process of this study, we also demonstrated in a separate publication (Gomes et al., 2022) that loss of function of EVs after SEC can be fully reverted by adding the SEC late fraction. Corona formation was indicated by means of fluorescent albumin as a model protein (Gomes et al., 2022).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As a proof of concept, we visualised the corona formation by super‐resolution microscopy using fluorescent albumin and fluorescent VEGF. During the review process of this study, we also demonstrated in a separate publication (Gomes et al., 2022) that loss of function of EVs after SEC can be fully reverted by adding the SEC late fraction. Corona formation was indicated by means of fluorescent albumin as a model protein (Gomes et al., 2022).…”
Section: Discussionsupporting
confidence: 60%
“…For statistical analysis, three fields of view were acquired for three independent donors. To visualise the protein corona around EVs, EV TUCF coated with a fluorescent albumin‐AF488 or VEGF‐CF488A corona were stained with tetraspanin CD9, (R&D Systems, USA) CD63, (Becton Dickinson, USA) and CD81 (R&D Systems, USA), all conjugated to Alexa flour 647 (tetramix) as published (Gomes et al., 2022). Quantification of colocalizations was performed as reported with a limit of 150 nm radius and five localizations for quantifying an event as colocalization.…”
Section: Methodsmentioning
confidence: 99%
“…The immunomodulatory effects of EVs with or without IL-10 were evaluated in stimulated T-cells ( 21 23 ). Fresh human CD3+ Pan T-cells (4W-350, Lonza, Walkersville, MD, USA) were cultured in Roswell Park Memorial Institute (RPMI) 1640 medium (10-040-CM, Corning Life Sciences, Corning, NY, USA) supplemented with 10% FBS for 6hrs after been thawed.…”
Section: Methodsmentioning
confidence: 99%
“…The application of size exclusion chromatography is prevalent across laboratories worldwide (Royo et al, 2020) due to its gentle nature and efficiency for eliminating contaminating materials (Baranyai et al, 2015;Guan et al, 2020;Lobb et al, 2015;Stam et al, 2021). Based on the growth in the use of isolation techniques that preserve EV integrity and prevent EV aggregation (Royo et al, 2020), as well as recent reports of the application of tangential flow filtration (Andrade et al, 2021;Binder et al, 2021;Busatto et al, 2018;El Baradie et al, 2020;Haraszti et al, 2018;Heinemann et al, 2014) coupled with size exclusion chromatography (Coenen-Stass et al, 2019;Corso et al, 2017;Gomes et al, 2022;Mcnamara et al, 2018;Nordin et al, 2019;Wolf et al, 2022), it can be anticipated that this combinatorial method may become standard for many laboratories in the near future.…”
Section: Introductionmentioning
confidence: 99%